Establishment of Omnibus Law in Solving Investment Issues in Indonesia - Putro, Tri Anggoro (Universitas Muhammadiyah Yogyakarta, 2021)
This study aimed to better understand the concept of Omnibus Law in the legislation and evaluate its use in responding to investment needs in Indonesia. The method in this research was normative legal research with secondary data through data analysis. This study showed that the Omnibus Law was not an appropriate approach to the formation of legislation in responding to investment needs in Indonesia. Based on the existing data, the investment climate in Indonesia is quite high and running well and even in a better situation when compared to other Asian countries. The Omnibus Law on Job Creation will raise a new problem instead, such as the absence of legal certainty for investment and the priority of the investment types. From the aspect of industrial relations, the Omnibus Law will result in disharmony in industrial relations between employers and workers, and it even potentially reduces guarantees for workers' human rights. Ironically, the fulfillment of workers' human rights has become an important benchmark for investors in developed countries to invest in developing countries, such as Indonesia. Therefore, the Indonesian government should strengthen the Corruption Eradication Commission and ensure a better investment climate by guaranteeing human rights to all workers and by reducing the ratio between investments (ICOR).